Improving the Quality of Life of the Elderly With Complementary Herbal Therapy Education - Nurhafni Nurhafni (International Journal of Health and Social Behavior, 2024)
This study explores the impact of complementary herbal therapy education on improving the quality of life in the elderly. As aging populations face increasing health challenges, there is a growing interest in alternative approaches that can enhance well-being. Herbal therapy, a practice rooted in traditional medicine, offers potential benefits for managing chronic conditions and promoting overall health in older adults. The research involved educating elderly participants about the use of specific herbal remedies tailored to common geriatric issues, such as arthritis, digestive problems, and sleep disturbances. Pre- and post-intervention assessments were conducted to measure changes in physical health, emotional well-being, and daily functioning. The results revealed significant improvements in the participants' quality of life, with notable reductions in symptoms, enhanced vitality, and increased satisfaction with their health management. The study concludes that educating the elderly about safe and effective use of herbal therapy can serve as a valuable complement to conventional treatments, leading to better health outcomes and improved quality of life. Further research is recommended to refine educational strategies and explore the long-term benefits of herbal therapy in the elderly population.